2020
DOI: 10.1111/1755-0998.13277
|View full text |Cite
|
Sign up to set email alerts
|

A powerful long metabarcoding method for the determination of complex diets from faecal analysis of the European pond turtle (Emys orbicularis, L. 1758)

Abstract: High‐throughput sequencing has become an accurate method for the identification of species present in soil, water, faeces, gut or stomach contents. However, information at the species level is limited due to the choice of short barcodes and based on the idea that DNA is too degraded to allow longer sequences to be amplified. We have therefore developed a long DNA metabarcoding method based on the sequencing of short reads followed by de novo assembly, which can precisely identify the taxonomic groups of organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 94 publications
0
9
0
Order By: Relevance
“…Our study represents one of only a few complete dietary analyses of omnivores using DNA metabarcoding (but see De Barba et al, 2014; Ducotterd et al, 2021; Robeson et al, 2018; Silva et al, 2019) and the first study examining the omnivorous diet of a threatened endemic reptile. We found that Telfair's skinks consume a few species regularly and many species rarely.…”
Section: Discussionmentioning
confidence: 99%
“…Our study represents one of only a few complete dietary analyses of omnivores using DNA metabarcoding (but see De Barba et al, 2014; Ducotterd et al, 2021; Robeson et al, 2018; Silva et al, 2019) and the first study examining the omnivorous diet of a threatened endemic reptile. We found that Telfair's skinks consume a few species regularly and many species rarely.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA extraction was performed on approximately 100 mg of material, with the QIAamp® PowerFecal® DNA kit (Qiagen GmbH, Hilden, Germany) according to the manufacturer's protocol. The concentration and the quality of the extracted DNA were evaluated using a NanoDrop™ 1000 spectrophotometer (Thermo Fischer Scientific, Switzerland) and a Qubit® 3.0 Fluorometer (Thermo Fischer Scientific) (Ducotterd et al, 2021).…”
Section: Dna Extraction and Reference Sequence Databasementioning
confidence: 99%
“…We used the long metabarcoding method developed by (Ducotterd et al, 2021) from which we only retained the combination of primers pairs targeting the mitochondrial-encoded cytochrome oxidase subunit I (COI) gene. Namely, ModRepCOI-F and ModRepCOI-R (Reeves et al, 2018), COI-CO2 and COI-CO4 (Che et al, 2012), ODO-LCO1490d and ODO-HCO2198d (Dijkstra et al, 2014) and mlCOIintF and jgHCO2198 (Leray et al, 2013).…”
Section: Long Dna Metabarcoding Resolution and De Novo Assemblymentioning
confidence: 99%
See 2 more Smart Citations